Sleep and Coping in Early Childhood During the COVID-19 Pandemic - Lokhandwala, Sanna; Holmes, Jennifer F.; Mason, Gina M.; St. Laurent, Christine W.; Delvey, Cassandra; Hanron, Olivia; Andre, Chloe; Rodheim, Katrina; Kaur, Sukhmanjit; Spencer, Rebecca M. C. (Frontiers in Pediatrics, 2021)
Sleep disturbances in early childhood are associated with mood and anxiety disorders. Children also exhibit sleep disruptions, such as nighttime awakenings, nightmares, and difficulties falling asleep, in conjunction with adverse events and stress. Prior studies have examined independently the role of sleep on adaptive processing, as well as the effects of stress on sleep. However, how childhood sleep and children's adaptive behavior (i.e., coping strategies) bidirectionally interact is currently less known. Using a within-subjects design and actigraphy-measured sleep from 16 preschool-aged children (Mage = 56.4 months, SD = 10.8, range: 36–70 months), this study investigated how prior sleep patterns relate to children's coping during a potentially stressful event, the COVID-19 pandemic, and how prior coping skills may influence children's sleep during the pandemic. Children who woke earlier had greater negative expression both before and during the pandemic. During the pandemic, children slept longer and woke later on average compared to before the pandemic. Additionally, for children engaged in at-home learning, sleeping longer was associated with less negative expression. These findings highlight how sleep behaviors and coping strategies are related, and the stability of this relationship under stress.